Association of eating out with bone density in Taiwan. Issue 17 (29th August 2017) - Huang, Yu-Hung; Lin, Chao-Cheng; Lin, Ching-I; Lin, Shyh-Hsiang
Abstract: Objective: The present study analysed data derived from the 2004–2008 Nutrition and Health Survey in Taiwan, conducted by the Ministry of Health and Welfare, to understand the relationship among eating-out behaviour, related non-nutritional factors and osteopenia in the Taiwanese population. Design/Setting/Subjects: Data of 1140 adults who had been evaluated with dual-energy X-ray absorptiometry in June 2007 were included. The data were analysed through descriptive and inferential statistics to determine the association of osteopenia with the frequency of eating out, demographic variables (i.e. age, sex, level of education, marital status and place of birth), BMI, waist circumference and food consumption. Results: Gender, age, education level, personal income and waist circumference were all factors found to be significantly associated with eating-out frequency and the incidence of osteopenia. Eating-out frequency was negatively associated with the incidence of osteopenia. Individuals with BMI>27 kg/m 2 had a lower frequency of eating out and a lower incidence of osteopenia. Individuals with a lower monthly income had a significantly greater chance of developing osteopenia. Men living without spouses had significantly higher chances of osteopenia. Ca intake was negatively associated with breakfast eating-out frequency. Conclusions: Eating-out frequency was not associated with an increasing incidence of osteopenia, but affected the Ca intake in the Taiwanese population. Having a balanced selection of food is crucial to reduce the incidence of osteopenia. Improving nutritional knowledge for those under higher risk of osteopenia is necessary to prevent osteopenia and Ca deficiency.